Effects of music on the preoperative and intraoperative anxiety through the assessment of pupil size and vital signs (blood pressure, respiratory, and pulse rates) among cataract surgery patients at UNTH-Enugu - Ezepue, Chukwubuike Obiora; Anyatonwu, Obinna Princewill; Duru, Christian Chukwuka; Odini, Franklin; Nwachukwu, Nkiru Zuada; Onoh, Chidimma; Nwachukwu, Nwamaka; Oguonu, Chukwunonso Afam (Frontiers in Ophthalmology, 2024)
Background/Aim To examine how music can impact preoperative and intraoperative anxiety via assessment of physiological markers such as pupil size, blood pressure, pulse rate, and respiratory rate. Methods This is a randomized interventional study of individuals aged 50 years and above who were scheduled for and undergoing cataract surgery under regional anesthesia, with music (test group) randomly matched with similar individuals undergoing the same procedure but without music (control group). The surgeries were performed in the operating theater of the Department of Ophthalmology, University of Nigeria Teaching Hospital (UNTH), Ituku-Ozalla, Enugu. Using a systematic random sampling method, a total of 98 patients were grouped into two. Both groups completed the State–Trait Anxiety Inventory (STAI) questionnaire at baseline, immediately upon entrance into the preoperative room and 5 min after intervention. Relevant study indices (blood pressure, pulse, respiratory rate, and pupil diameter) were measured and recorded, and these served as baseline parameters. The STAI questionnaire was then administered. Results were analyzed using the SPSS version 20 and analysis of variance was used to compare means of variables measured at baseline, preoperative before intervention, and preoperative after intervention. Categorical variables were compared using the Chi-square test. Student’s t-test was used to analyze the continuous variables. Results Our analysis, using the multiple linear regression, showed that music has an effect on preoperative anxiety and intraoperative anxiety by positively affecting the blood pressure, pulse rate, respiratory rate, and pupil diameter (P ≤ 0.001). Conclusion Music reduces preoperative and intraoperative anxiety evidenced by its effect on the physiological biomarkers.